A Forest Cover Classification System Using Remotely Sensed Data - Singh, Ashbindu (Indian Forester, 1988)
In this paper a forest cover classification system for use with remote sensor data suitable for Indian conditions has been proposed. The classification system takes into account the nature of remotely sensed data and is based on the parameter which can be directly interpreted on imagery or factors which effect the spectral response that are recorded by the sensor.